Simulations in the political science classroom : games without frontiers - Harvey, Mark, 1969-; Fielder, James; Gibb, Ryan (New York, NY : Routledge, 2022)
"This book is premised on the assumption that games and simulations provide welcome alternatives and supplements to traditional lectures and class discussions, especially in political science classrooms where real world circumstances provide ideal applications of theory and policy prescriptions. Implementing such an active learning program, however, is sometimes daunting to overburdened professors and teaching assistants. This book addresses the challenges of using games and simulations in the political science classroom, both online and in person. Each chapter offers a game or simulation that politics teachers can use to teach course concepts and explains ways to execute it effectively. In addition, the authors in this volume make a proactive case for games and simulations. Each chapter offers research to evaluate the effectiveness of the activity and pedagogical design best practices. Thus, the book not only serves as a game design resource, but also offers demonstratable support for using games and simulations in the political science classroom. Aimed at teachers at all levels from high school through college, the book may be especially appealing to graduate students entering teaching for the first time and open to new teaching and learning approaches"--
Keywords: Political science -- Study and teaching; Video games in education; Political science -- Computer-assisted instruction; POLITICAL SCIENCE / Government / National; EDUCATION / Teaching Methods & Materials / Social Science; POLITICAL SCIENCE / History & Theory